Influence Sources of Project and Functional Managers in Matrix Organizations - Dunne, Edward; J.Stahl, Michael; Melhart, Leonard J. (Academy of Management Journal, 1978)
The article discusses a study which examined the influence of or authority structure in a military matrix organization which contains projects. Different power bases as sources of influence are described as legitimate power, reward power, coercive power, expert power, and referent power. The author points out several important techniques which project managers use to supplement authority such as technical competence and persuasiveness. The hypotheses addressed by the study of the perceptions of military organizations of the influence sources of both their project manager and their functional manager are examined. The article also covers the reasons for compliance with project managers and functional managers.